Macroeconomic evaluation of climate change model (MECC-Model): The case study of China - Ruiz Estrada, Mario Arturo (2013)
Global climate change has a potentially large impact on economic growth but measuring their economic impact is subject to a great deal of uncertainty. The central objective of our paper is to set forth a model – the macroeconomics evaluation of climate change (MECC) model – to evaluate the impact of climate change on GNP growth. The model is based on five basic indicators – (i) the climate change growth rates (αi); (ii) the national climate change vulnerability rate (ΩT); (iii) the climate change magnitude rate (Π); (iv) the economic desgrowth rate (δ); (v) and the CC-Surface. In addition, we apply the MECC Model to the case of China to evaluate its impact on the Chinese economy.